STUDY OF FACTORS RELATED TO THE DISCONTINUATION OF IUCD USAGE - Muzammil, Khursheed; Kishore, Surekha; Garg, B S (Indian Journal of Community Health, 2011)
Background: Various studies conducted in the past have shown high rates of discontinuation of IUCD especially in rural areas but very few studies have been conducted for determining the responsible contributing factor for the same. It has been emphasized that there is an urgent need to increase its use for which we have to plan the quality of services. Objective: To find out the factors related to the discontinuation of IUCD usage. Methodology: The present cross-sectional study was carried out in the 5 villages around Sewagram of District Wardha by interviewing women currently using or those who have ever used IUCD in the past two years. The data was recorded in a structured and pre-tested proforma and subsequently analyzed. Results: About 20% of women were found to be IUCD acceptors in the last two years of which 43.48 % were using IUCD currently and 56.52% had ever used them in the last two years. Maximum women got it inserted at the institute. Main reasons for discontinuation of IUCD as cited by women were excessive bleeding per vaginum (39.68%), abdominal pain (38.62%), low backache (35.97%), and weakness (28.04%). Conclusion: Increasing the awareness about the importance and benefits of IUCD will be very much helpful in its high acceptance along with providing quality health services. Keywords: IUCD usage, side effects, IUCD discontinuation.